Upaya Meningkatkan Produktivitas Anak-Anak Pada Masa Pandemi Covid-19 Melalui Kegiatan Positif di Bagor Kulon - Is Damayanti; Nurul Dwi Lestari (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
During the covid-19 pandemic in Indonesia, the number of people infected with the covid-19 virus is increasing. This has an impact on many aspects of everyone’s life, whether in education, health, social, economic. In school children, learning is carried out boldly using mobile phones at home. This makes the mind saturated, the purpose of this community service is to eliminate boredom by increasing the productivity of children during the covid-19 pandemic through this positive service activity using the Participatory Action Research (PAR) method. This community service activity is aimed at school-age children in Bagor Kulon village. The application of various positive activities for school-age children can make them more productive so that the mind is calmer and eliminates boredom. Activities that can be applied include fishing by reading and writing IQRA, learning to memorize letters, reading a book, and small competitions including adhan competitions, poetry reading competitions, and short letter memorization competitions, and short letter memorization competitions. Activities are carried out with due observance of health protocols. As a result of community service through these positive activities, children have high enthusiasm to do positive activities and get positive benefits.